SEP Monitoring Analysis of Outpatients in Medicare to Support the Effectiveness of BPJS Patient Services - Sari, Irda; Dwi Ariani, Nurul; Nur Wahidah, Zahrah (Dinasti Research & Yayasan Dharma Indonesia Tercinta (DINASTI), 2024)
Monitoring is a monitoring process in the Medicare system to prevent participant eligibility letters from not being formed. The aim of this research is to analyze the monitoring system for outpatient Participant Eligibility Letters to support the effectiveness of services for BPJS patients. The research method uses descriptive qualitative, data collection uses observation and interviews, data validation uses source and technique triangulation techniques. Based on the results of the interviews, researchers still found several obstacles that prevented the formation of Participant Eligibility Letters, analyzed using 6M+1I, namely in (1) man, namely copying and pasting the SEP number in the wrong column, copying and pasting someone else's SEP number to Medicare, the patient has not been fingerprinted, the card number is inactive or the data on the BPJS and KTP do not match; (2) machine, the system is still unable to fully read the error when processing the SEP on Medicare. The analysis of the SEP monitoring process is in accordance with the SPO guidelines, the benchmark for outpatient clinics is that the SEP has been formed and new patients can be served until the end of the service.